Preparation of carbon supported catalyst from cattail leaves for biodiesel fuel upgrading application. (2019) - Jaruwat, Dolrudee; Udomsap, Parncheewa; Chollacoop, Nuwong; Eiad-ua, Apiluck
Abstract: Carbon supported catalyst have been successfully synthesised from cattail leaves via hydrothermal carbonization for biodiesel fuel upgrading. This research study the effect of hydrothermal temperature (160-200 °C), reaction time (4-12 h) and influence of co-solvent such as CH3 OH, C2 H5 OH, H2 SO4, and HCl treatment to porosity and surface area of carbon material. The sample have been characterized by scanning electron microscopy, nitrogen sorption, fourier transform infrared spectroscopy were employed to characterize morphology, specific area (SBET ), and surface function, respectively. The results revealed that hydrothermal-carbonization process and co-solvent treatment have effect on the properties of supported carbon. The hydrothermal temperatures and time were increased resulted in the surface area and pore volume of supported carbon gradually increased leading to increasing metal distribution on the surface of supported carbon. It can be implied that the catalyst is good catalytic activity.